2022
DOI: 10.3389/fpsyg.2022.1014655
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive ability on academic achievement: The mediating role of self-discipline and the moderating role of planning

Abstract: In this study, 572 secondary school students aged 15–18 years old stage were selected to study the effect of their cognitive ability and self-discipline and planning on academic achievement. Cognitive ability was classified into memory ability, representational ability, information processing ability, logical reasoning ability, and thinking conversion ability, and analyzed the effects of these five ability values on academic achievement. The mediating effect of self-discipline ability between cognitive ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Similarly, a study in a non-Mediterranean country showed the same direction [ 17 ]. One possible explanation for this association may be the well-documented relationship between cognitive performance and academic achievement [ 14 , 15 ]. In this case, MedDiet may play a mediating role in the relationship between cognitive performance and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study in a non-Mediterranean country showed the same direction [ 17 ]. One possible explanation for this association may be the well-documented relationship between cognitive performance and academic achievement [ 14 , 15 ]. In this case, MedDiet may play a mediating role in the relationship between cognitive performance and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has consistently shown that cognitive performance has a direct impact on academic achievement [ 14 , 15 ]. In this sense, previous studies indicate that higher adherence to the MedDiet was associated with greater academic achievement in children and adolescents [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The academic achievement in geography, as a significant manifestation of the outcomes of geography education, has always been a topic of interest to geographers, psychologists, and educators. In the field of cognitive science, academic achievement is often seen as behavior driven by cognitive factors [6]. With the development of cognitive science, many detailed theories can be used to explain the relationship between academic motivation and academic achievements, such as self-efficacy theory [7,8], achievement goal theory [9], and attribution theory [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A technique or countermeasure aimed at enhancing training should be robust to these stressors and not further burden the crew. It is theorized that improved performance in cognitive tasks can impact learning ability (Ackerman et al, 1995;Shi and Qu, 2022). A potential training technique focused on enhancing cognitive functioning is computerized cognitive training (CCT), where subjects exercise specific cognitive concepts through computerized games in hopes of training mental ability (Jaeggi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%